2014
DOI: 10.1089/ars.2013.5304
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Sulfide Targets EGFR Cys797/Cys798 Residues to Induce Na+/K+-ATPase Endocytosis and Inhibition in Renal Tubular Epithelial Cells and Increase Sodium Excretion in Chronic Salt-Loaded Rats

Abstract: Aims: The role of hydrogen sulfide (H 2 S) in renal sodium and water homeostasis is unknown. We investigated whether H 2 S promoted Na + /K +

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…Analyzing the EGCG binding with the wild type EGFR, one preferential and favorite binding pose was found, involving directly the ATP binding pocket ( Figure 7A) in agreement with experimental results. Due to the high number of OH groups of this catechin, five different Hbond interactions were found, involving Ile744, Gly796, Asn842 and Asp855 residues, and in particular with Cys797, which is very important for the EGFR inhibition as already demonstrated in other studies [40]. In addition, further hydrophobic interactions with different aminoacid residues were observed ( Figure 7B).…”
Section: Erl and Egcg Binding Mode With Egfr Wild Typesupporting
confidence: 64%
“…Analyzing the EGCG binding with the wild type EGFR, one preferential and favorite binding pose was found, involving directly the ATP binding pocket ( Figure 7A) in agreement with experimental results. Due to the high number of OH groups of this catechin, five different Hbond interactions were found, involving Ile744, Gly796, Asn842 and Asp855 residues, and in particular with Cys797, which is very important for the EGFR inhibition as already demonstrated in other studies [40]. In addition, further hydrophobic interactions with different aminoacid residues were observed ( Figure 7B).…”
Section: Erl and Egcg Binding Mode With Egfr Wild Typesupporting
confidence: 64%
“…Consistent with this idea, a recent study demonstrated reduced granule exocytosis in H 2 S-exposed platelets, which may be due to interference of H 2 S with SNARE-mediated vesicle exocytosis (34). Aside from the trafficking machinery, the translocation of ENaCcontaining vesicles in lung epithelial cells may involve additional, yet unidentified, pathways involving protein tyrosine kinase (8,51,90), and H 2 S has recently been implicated in the modulation of tyrosine kinase-dependent signaling pathways (32,78).…”
Section: ϫ5mentioning
confidence: 72%
“…The enzyme D-amino acid oxidase constitutes an additional enzymatic pathway for H 2 S production and is highly expressed in mammalian kidneys (Shibuya et al, 2013). In mammals, endogenous H 2 S is proposed to be important for normal kidney function (Lobb et al, 2015) and H 2 S has been shown to increase glomerular filtration rate (Xia et al, 2009) and salt excretion by inhibition of Na + /K + -ATPase (Ge et al, 2014), and to suppress renin release (Cao and Bian, 2016). Given that H 2 S is an ancient vasoregulatory molecule across multiple vertebrate clades (Dombkowski et al, 2004), our data indicate that H 2 S could also have a similar regulatory role in the renal function of turtles.…”
Section: Resultsmentioning
confidence: 99%